Respuesta :

Answer:

[tex]a_n = 49(3)^{n-1}[/tex]

Step-by-step explanation:

A recursive rule for a geometric sequence is a1=49;an=3an−1

First term a1= 49

[tex]a_n=3*a_{n-1}[/tex]

[tex]a_2=3*a_{1}[/tex]

[tex]a_2=3*49}[/tex]

To get second term, multiply the first term by 3

So common ratio r = 3

Explicit rule for geometric sequence is

[tex]a_n = a_1(r)^{n-1}[/tex]

a1= 49  and r= 3

So explicit rule is

[tex]a_n = 49(3)^{n-1}[/tex]

Answer:

(4/9)(3)^n-1

explanation:

i like turtles and i know eberatang